Quality of Life of Mothers of Children with Intellectual Disability: Do Social Support, Maternal Stress and Socio-Economic Status Play a Role? - Udeme Samuel Jacob; Jace Pillay; Bolanle Misitura Oyundoyin (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
This study investigate the influence of perceived social support, maternal stress and socio-economic status on quality of life of mothers of children with intellectual disability, Oyo State, Nigeria. A total of 93 mothers of children with intellectual disability were respondents to a structured questionnaire. Findings revealed that perceived social support and socio-economic status had significant positive relationship with quality of life of mothers of children with intellectual disability. Result showed that the relationship between maternal stress and quality of life was negative and significant. Moreover, the study revealed that perceived social support had the highest relative contribution on quality of life of mothers followed by socio-economic status while the least was by maternal stress. Furthermore, the joint contribution of perceived social support, maternal stress and socio-economic status on quality of life of mothers was significant; therefore, the three variables should be given proper consideration so as to enhance quality of life mothers of children with intellectual disability.